Conocimiento y práctica de prevención de accidentes domésticos en madres con niños de 3 a 5 años Institución Educativa Inicial Mi Carrusel Iquitos 2025 - Garcia Torres, Maria Isabel (2025)
The main objective of this study was to investigate the relationship between the level of knowledge and the level of practice regarding the prevention of domestic accidents among mothers with children aged three to five years attending the Mi Carrusel Iquitos 2025 early childhood education center. The research was conducted using a quantitative methodology, and the design was descriptive, correlational, cross-sectional, and generally non-experimental. A total of 84 mothers were included in the sample. The knowledge questionnaire and the Likert scale were the tools used in the process of preventing accidents that occur within the home. The chi-square (X²) statistical test was used to perform a correlation analysis, and SPSS version 27.0 software in Spanish was used for data analysis. It was found that 57.1% of the mothers had a high level of knowledge about the prevention of domestic accidents in children aged 3 to 5 years, while 17.9% of the mothers had a poor level of knowledge. This conclusion was based on the results of the study. 76.2% of the mothers had adequate practices for preventing falls, burns, poisonings, and suffocation, while 23.8% had inadequate practices. The calculated value of X² = 19.934, with a p-value less than 0.001 and a significance level of α = 0.05, was obtained by analyzing the correlation between the two variables. In the field of accident prevention, there is a statistical correlation between knowledge and the measures adopted.